Prognostic significance of neuron-associated protein expression in non-muscle-invasive urothelial bladder cancer. Issue 8 (28th July 2009) - Mhawech-Fauceglia, P; Ali, L; Cheney, R T; Groth, J; Herrmann, F R
Abstract : Background: Numerous novel genes have been identified in urothelial bladder cancer (UBC); genes including ninjurin, synuclein and neuropilin seem to be associated with invasive tumours and aggressive behaviour. Aims: To define the protein expression of these biomarkers and to reveal their prognostic value in a large series of superficial (pTa) and minimally invasive (pT1) cases of UBC with a long and adequate follow-up. Methods: Tissue microarray was done on 183 paraffin-embedded tumour tissues (pTa 81, pT1 102). Statistical analysis was performed to define the association between each of these biomarkers, clinical data and tumour outcomes. Results: There was a statistically significant association between synuclein expression and tumour stage (p = 0.029). Ninjurin expression was significantly associated with tumour progression in univariate analysis. Tumour grade seemed to have an independent value in predicting tumour recurrence and progression. Conclusion: Tumours with strong synuclein expressions are more likely to be more advanced tumours (pT1). Tumours expressing ninjurin tend to progress slower than those with no ninjurin expressions. Synuclein and neuropilin failed to show any value in predicting tumour behaviour.